An application of the new function method to the Zhiber–Shabat equation - Tolga Aktürk; Yusuf Gürefe; Yusuf Pandır (An International Journal of Optimization and Control: Theories & Applications, 2017)
This paper applies a new approach including the trial equation based on the exponential function in order to find new traveling wave solutions to Zhiber-Shabat equation. By the using of this method, we obtain a new elliptic integral function solution. Also, this solution can be converted into Jacobi elliptic functions solution by a simple transformation.